PP172 Recruiting Academic Physicians Without Financial Conflict Of Interest. (12th January 2018) - Belghiti, Jacques; Fuks, David; Emery, Gregory; Luzio, Stéphanie
Abstract : INTRODUCTION: To minimize the potential impact of conflicts of interest on health recommendations, several health institutions may be reluctant to recruit academic physicians due to their potential close relationship with industry. The present study aimed at evaluating the influence of academic physicians (AP) on the "rate of deport" due to financial support in the national commission of the HAS assessing medical devices. METHODS: After the renewal of this commission in November 2015, introducing patients representatives and more academic physicians, two periods of 12 months immediately before and after that date have been compared regarding the rate of deport during the sessions. Deport were decided by the legal section of our institution one week before each meeting according to a complete analysis of potential financial conflict of interest related to the medical device assessed. Only members without significant financial conflicts were allowed to participate to the discussion and the vote. The assessment of potential conflict of interest of all members followed the same criteria during the two periods. RESULTS: The number of physicians increased in the second period (nineteen versus twenty-three) with a significant higher rate of academic physicians (63 percent versus 82 percent, p = .001). The mean attendance of physicians was significantly lower during the second period (80 percent versus 65 percent, p = .03). During the two periods, the number of meetings (n = 22) was similar and the number of dossiers assessing new products was comparable (96 versus 104, p = .872). The decision to reimburse the medical devices was similar in the two periods (78 percent versus 73 percent, p = .681). The number of cases when physicians' members were deported for conflict of interest was similar during the two periods (30 versus 28, p = .482) with not any increase among academic physicians. CONCLUSIONS: This study showed that it is possible to recruit several academic physicians without major financial conflicts of interest providing that their status could alter their assiduity.